Pengaruh Celengan Padjeg terhadap Kepatuhan WP Dengan Motivasi WP Sebagai Variabel Intervening (Studi Kasus Di Wilayah Kerja KPP Wonosari) - Suyanto, Suyanto (AKMENIKA, 2018)
This study aims to determine the effect of Celengan Padjeg Program, on taxpayer compliance with taxpayer motivation as an inetervening variable. The population used is 116 taxpayers who have received the Celengan Padjeg Program in the working area of KPP Pratama Wonosari with a total sample of 89 respondents and 80 questionnaires that can be processed. The analysis tool used is multiregression with path analysis as a method of analysis of mediation variables. The result, Celengan Padjeg Program can have a significant positive effect directly on taxpayers motivation but not for taxpayers compliance. In addition, taxpayers Motivation can have a significant positive effect on taxpayers compliance. Finally, the Celengan Padjeg Program can have a significant positive effect through taxpayers motivation on taxpayers compliance with taxpayers motivation as a significant intervening variable mediating the Celengan Padjeg Program on taxpayers compliance.Keyword: Celengan Padjeg Program, Compliance, Motivation